2011
DOI: 10.1016/j.jelechem.2011.07.041
|View full text |Cite
|
Sign up to set email alerts
|

A spectrophotometric and NMR study on the formation of an inclusion complex between dopamine and a sulfonated cyclodextrin host

Abstract: a b s t r a c tThe formation of an inclusion complex between the sulfonated b-cyclodextrin (Sb-CD) with dopamine (DA) was confirmed using UV-vis measurements and NMR methods. It was also established that a 1:1 complex was formed between the Sb-CD and the DA, where the inclusion occurred predominantly through the aromatic ring of the DA and the hydrophobic CD cavity. The results also suggest that a change in the anion, of supporting electrolyte, had an influence on the DA-Sb-CD complexation while no change was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…A slight bathochromic shift (2~3 nm) was observed with increasing concentrations of HPβCD (Fig. S7), which has been reported previously with other guest molecules and has been explained in terms of a change in the environment of the molecule as it is included within the CD cavity (Hendy and Breslin, 2011;Lin et al, 2020). Usually, O3 would have been completely degraded after 1-3 hour in DI water (Dettmer et al, 2017), however in this study, absorption peaks were still observed even after 12 h in the presence of HPβCD (Fig 5a and Fig.…”
Section: Characterisation Of Inclusion Complexessupporting
confidence: 82%
“…A slight bathochromic shift (2~3 nm) was observed with increasing concentrations of HPβCD (Fig. S7), which has been reported previously with other guest molecules and has been explained in terms of a change in the environment of the molecule as it is included within the CD cavity (Hendy and Breslin, 2011;Lin et al, 2020). Usually, O3 would have been completely degraded after 1-3 hour in DI water (Dettmer et al, 2017), however in this study, absorption peaks were still observed even after 12 h in the presence of HPβCD (Fig 5a and Fig.…”
Section: Characterisation Of Inclusion Complexessupporting
confidence: 82%
“…This may indicate that the PPy-sβ-CD has some selectivity in relation to the uptake of DA and this can be explained by the formation of an inclusion complex between DA and the CD. The formation of this inclusion complex is facilitated by the electrostatic interactions between the protonated amine group of DA and the anionic pendants of the CD, while the more hydrophobic aromatic ring structure fits into the cavity of the cyclodextrins [40,41]. It is also clear from Fig.…”
Section: Discussionmentioning
confidence: 89%
“…3(a). While the sβ-CD provides a high charge facilitating a strong electrostatic interaction with the protonated DA, an inclusion complex can also be formed [40,41]. This inclusion complex, where the DA molecule is included in the cavity, appears to protect the molecule from oxidation and degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Hendy and Breslin, 2011 have investigated the complexation of dopamine (guest) and sulfated cyclodextrin (host) using ultraviolet (UV) and nuclear magnetic resonance spectroscopy (NMR) spectroscopy where they confirmed that the aromatic group of dopamine fits into the hydrophobic cavity based on the data obtained from spectroscopic techniques. [11] Several spectroscopic techniques can be used to investigate the inclusion complex formation. In UV spectroscopy, the change in spectrum increase or decrease in absorption intensity with varying concentrations of host moiety can give information about the complexation of the guest molecules with the host.…”
Section: Host-guest Interactions: Inclusion Complex Formationmentioning
confidence: 99%